2018
DOI: 10.1097/mpg.0000000000001991
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Liver Transplant Teams Coping With Patient Death

Abstract: Overall, formal supports were inconsistently offered to pediatric transplant team members. Team members expressed high acceptability for debriefing, which has been associated with benefits in other populations, and findings indicated better coping in the transplant setting when it was offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The results indicated no statistically significant differences in PTSI symptoms between groups at pre- or post-intervention, and a reduction in alcohol consumption one-month post-intervention for the active groups relative to the control group was not sustained at follow up. There were three studies that reported no statistically significant differences in mental health outcomes between those who did and did not have access to debriefing [ 28 , 29 , 30 ]. There was one study [ 27 ] that reported participants ( n = 57) who received organizationally-offered or -facilitated 90 min debriefing (having to attend a group session, individual meeting with a psychologist, or both) reported higher perceived event-related stress and PTSD scores than non-debriefed participants at a 5 year follow up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results indicated no statistically significant differences in PTSI symptoms between groups at pre- or post-intervention, and a reduction in alcohol consumption one-month post-intervention for the active groups relative to the control group was not sustained at follow up. There were three studies that reported no statistically significant differences in mental health outcomes between those who did and did not have access to debriefing [ 28 , 29 , 30 ]. There was one study [ 27 ] that reported participants ( n = 57) who received organizationally-offered or -facilitated 90 min debriefing (having to attend a group session, individual meeting with a psychologist, or both) reported higher perceived event-related stress and PTSD scores than non-debriefed participants at a 5 year follow up.…”
Section: Resultsmentioning
confidence: 99%
“…All of the 14 studies received at least one high risk or unclear rating on the strength of evidence criteria. One study was rated moderate to high quality [ 35 ], nine studies were of moderate to low quality [ 27 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 ], and four studies were of low quality [ 28 , 29 , 30 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, while caring for the young and terminally ill may bring with it positive effects such as the cultivation of a more compassionate attitude, enhanced job satisfaction and a chance to hone their psychosocial and interpersonal skills, the detrimental effects are far more jarring. The findings reveal that a physician’s moral, 90,91 existential, 79 emotional 78,82,92 -94 and psychological 80 state may be negatively affected with repercussions on their thinking, 84,89,95,96 decision making, 82,97,98 behavior, 93,99 spiritual ties, 100,79 professional roles 78,97 and personal relationships. 85,101,102 Data also suggests a physical element to these experiences.…”
Section: Resultsmentioning
confidence: 98%